A Response to ‘One Asia, or Many? Reflections from connected history’ - Herzig, E (Cambridge University Press, 2016)
The idea of Asia as a unity has appealed both to Europeans interested in differentiating themselves from a threatening if inferior Asiatic ‘other’, and to Asians keen to mark their distance from an alien and alienating Europe and West. For both groups, Asia is a useful term of alterity, although the place of ‘us’ and ‘them’ is reversed. Near the beginning of his lecture Sanjay Subrahmanyam remarks that, ‘in the play between the –emic and the –etic, the insider’s and the outsider’s perspective, a concept like “Asia” falls decidedly on the side of the –etic’. This point is reinforced by the fact that the European concept of Asia goes back to the Ancient Greeks (as Subrahmanyam notes), whereas the interest of Asian insiders in the concept of a homogeneous Asia is a modern phenomenon, a reaction against the assumption of superiority inherent in western imperialism and neo-imperialism. In the case of both the European and the Asian conceptions, however, it is the viewpoint of the observer rather than the empirical features of what is observed that gives shape and meaning to the concept. I will use this short response to take a look at Asia from a third perspective, one that is neither fully in- nor out-sider in character, namely that of the early modern Armenians, whose travels took them across the length and breadth of Asia, and Europe too.